Dependence of ventilation image derived from 4D CT on deformable image registration and ventilation algorithms. (8th July 2013) - Latifi, Kujtim; Forster, Kenneth M.; Hoffe, Sarah E.; Dilling, Thomas J.; van Elmpt, Wouter; Dekker, Andre; Zhang, Geoffrey G.
Abstract : Ventilation imaging using 4D CT is a convenient and low‐cost functional imaging methodology which might be of value in radiotherapy treatment planning to spare functional lung volumes. Deformable image registration (DIR) is needed to calculate ventilation imaging from 4D CT. This study investigates the dependence of calculated ventilation on DIR methods and ventilation algorithms. DIR of the normal end expiration and normal end inspiration phases of the 4D CT images was used to correlate the voxels between the two respiratory phases. Three different DIR algorithms, optical flow (OF), diffeomorphic demons (DD), and diffeomorphic morphons (DM) were retrospectively applied to ten esophagus and ten lung cancer cases with 4D CT image sets that encompassed the entire lung volume. The three ventilation extraction methods were used based on either the Jacobian, the change in volume of the voxel, or directly calculated from Hounsfield units. The ventilation calculation algorithms used are the Jacobian, Δ V, and HU method. They were compared using the Dice similarity coefficient (DSC) index and Bland‐Altman plots. Dependence of ventilation images on the DIR was greater for the Δ V and the Jacobian methods than for the HU method. The DSC index for 20% of low‐ventilation volume for Δ V was 0.33 ± 0.03 ( 1 SD ) between OF and DM, 0.44 ± 0.05 between OF and DD, and 0.51 ± 0.04 between DM and DD. The similarity comparisons for Jacobian were 0.32 ± 0.03, 0.44 ± 0.05, and 0.51 ± 0.04, respectively, and for HU they were 0.53 ± 0.03, 0.56 ± 0.03, and 0.76 ± 0.04, respectively. Dependence of extracted ventilation on the ventilation algorithm used showed good agreement between the Δ V and Jacobian methods, but differed significantly for the HU method. DSC index for using OF as DIR was 0.86 ± 0.01 between Δ V and Jacobian, 0.28 ± 0.04 between Δ V and HU, and 0.28 ± 0.04 between Jacobian and HU, respectively. When using DM or DD as DIR, similar values were obtained when comparing the different ventilation calculation methods. The similarity values for the 20% high‐ventilation volume were close to those found for the 20% low‐ventilation volume. The results obtained with DSC index were confirmed when using the Bland‐Altman plots for comparing the ventilation images. Our data suggest that ventilation calculated from 4D CT depends on the DIR algorithm employed. Similarities between Δ V and Jacobian are higher than between Δ V and HU, and Jacobian and HU. PACS number: 87.57.nj